2013
DOI: 10.1111/are.12203
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of ammonia in Pacu fish (Piaractus mesopotamicus, Holmberg, 1887) at different temperatures levels

Abstract: Piaractus mesopotamicus juveniles (total length 12 AE 0.5 mm) were exposed to different concentrations of ammonia-N (un-ionized plus ionized ammonia as nitrogen), using the static renewal method at different temperature levels (15, 20 and 25°C) at pH 7. The 24, 48, 72, 96 h LC 50 values of ammonia-N in P. mesopotamicus juveniles were 5.32, 4.19, 3.79 and 2.85 mg L À1 at 15°C; 4.81, 3.97, 3.25 and 2.50 mg L À1 at 20°C; and 4.16, 3.79, 2.58 and 1.97 mg L À1 at 25°C respectively. The 24, 48, 72, 96 h LC 50 values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 39 publications
1
39
1
6
Order By: Relevance
“…This result suggested that mandarin fish could make better use of protein than grass carp in this condition. The ammonia‐N excretion was suggested as an index which might give some indication about mandarin fish culture, especially water quality management in intensive fish culture (Barbieri & Bondioli ), from the perspective of resource and environment‐friendly.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that mandarin fish could make better use of protein than grass carp in this condition. The ammonia‐N excretion was suggested as an index which might give some indication about mandarin fish culture, especially water quality management in intensive fish culture (Barbieri & Bondioli ), from the perspective of resource and environment‐friendly.…”
Section: Discussionmentioning
confidence: 99%
“…Haematological and serum protein profile has been used as a tool to evaluate fish welfare and disturbance on fish metabolism BARBIERI and BONDIOLI 2015). It can also be influenced by antinutritional factors, such as lectins presented in greater quantities in grain legumes, such as soybeans, peas and grasses.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the increase in temperature in aquatic animals induces the higher toxic effects under toxicity exposure (Patra et al 2015), because the high temperature elevates the diffusion rate, bioavailability, and chemical reactions of the aquatic animals (Delos and Erickson 1999). Barbieri and Bondioli (2015) also reported the lower LC 50 for the ammonia exposure of Pacu fish, Piaractus mesopotamicus by increasing water temperature, which means that the higher temperature causes the higher ammonia toxicity.…”
Section: Introductionmentioning
confidence: 93%